Neuroimaging and Intravenous Recombinant Tissue Plasminogen Activator in Acute Ischemic Stroke beyond 4.5 Hours: A Systematic Review - Muhammad Ramadhan Ghifari; Resa Budi Deskianditya; Pradana Nur Oviyanti; Yuki Fitria Maatisya; Vega Pratiwi Putri (AKSONA, 2025)
Highlight: Ischemic stroke is a major cause of disability and death globally, emphasizing the urgent need for timely and effective thrombolytic interventions within a narrow treatment window. Neuroimaging has the potential to extend the therapeutic window for IV rt-PA beyond 4.5 hours, allowing clinicians to identify patients with salvageable brain tissue for treatment. Extending the IV rt-PA treatment window with neuroimaging support can significantly improve outcomes in stroke patients, although careful risk assessment is crucial.   ABSTRACT Introduction: Current guidelines suggest giving intravenous recombinant tissue plasminogen activator (rt-PA) within 4.5 hours after acute ischemic stroke onset or the time the patient was last-seen-well. Patients often arrive at the hospital after 4.5 hours, making thrombolysis treatment challenging. It is crucial to examine expanding this timeframe beyond 4.5 hours of onset or last-seen-well. Objective: This systematic review intended to examine the effectiveness and safety of IV rt-PA in patients presenting to the hospital beyond 4.5 hours of onset or last-seen-well. Methods: We searched PubMed, Scopus, and ScienceDirect for studies on acute ischemic stroke patients treated with IV rt-PA alteplase beyond 4.5 hours of onset or last-seen-well. Outcomes comprised the Modified Rankin Scale (mRS) score, intracranial hemorrhage (ICH), symptomatic ICH, and mortality. We assessed the risk of bias using Cochrane Risk of Bias Vol 2 and ROBINS-I. Results: Eleven randomized controlled trials and observational studies were selected. Most subjects were above 65 years, and their baseline mean or median NIHSS scores were 6–12. Seven studies had specific neuroimaging criteria for eligibility, such as DWI/FLAIR or T2WI mismatch, PWI/DWI mismatch, or CT/MR perfusion. In RCTs, alteplase group had 47.1% to 53.3% favourable results (mRS 0-1) compared to 41.3% to 48.3% in placebo/controls group and 23% to 85% in observational studies. Compared to the placebp/control group and onset within 4.5 hours, alteplase typically had better ourcomes. However, ICH, symptomatic ICH, and mortality were numerically higher, albeit not statistically significant. Conclusion: IV rt-PA alteplase can be given  for up to 9-12 hours from onset or last-seen-well with neuroimaging evidence of salvageable tissue, such as the perfusion imaging RAPID criteria or DWI/FLAIR or T2WI mismatch, taking consideration of hemorrhage and mortality concerns.